Diagnostic Accuracy of Multi-Detector CT for Evaluation of Renal Masses - Mustafa Ali Siddiqui, Amjad Ali, Kanwal Khalid, Muhammad Ali Rabbani, Fareeha Naseer Syed, Syed Atif Hussain Andrabi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the accuracy of multi-detector computed tomography (MDCT) in differentiation of renal masses taking histopathology as gold standard. Methods: This cross-validation study was conducted from March 2021 to August 2021 at Al Hussain Diagnostic & Medical center Nishtar Road Multan. We included 100 patients presenting with renal masses on clinical and ultrasonography. All patients underwent MDCT for evaluation of renal masses. After MDCT, biopsy specimens were obtained for histopathological diagnosis of renal masses. The MDCT findings were correlated with histopathology diagnosis to determine the accuracy of MDCT. Results: Mean age was 45.8±12.36 years, 67% patients were male and 33% were female. Malignancy was diagnosed in 83% patients and remaining 17% patients were diagnosed of having benign lesions. Out of malignant lesions, 65% patients had RCC, 07% Wilm’s tumor, 6% lymphoma, meta-stasis was diagnosed 04% patients and 01% renal pelvic TCC. Among the benign lesions 11% patients had Angiomyolipoma and oncocytoma was diagnosed in 6.0% patients. The overall sensitivity of CT scan was 97.6%, specificity was 100%, PPV was 100% and NPV was 89.5%. Conclusion: MDCT can be used as the imaging method of choice for initial evaluation and diagnosis of RCC as it is associated with high sensitivity and specificity for differentiating malignant from benign lesions.